2013
DOI: 10.1007/s00467-013-2477-9
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy for the failed renal allograft in children: predictors and outcomes

Abstract: Children with Banff II rejection, an inflammatory response and early graft loss are more likely to require transplant nephrectomy. Nephrectomy may be associated with higher circulating HLA antibody levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The contribution of nephrectomy and/or continuing immunosuppression to HLA sensitisation in the failing graft is not clear. Transplants that fail in the first year, or those that result from acute non-concordance with medications often present with acute rejection and systemic involvement, and frequently progress to nephrectomy; it is perhaps not surprising, therefore, that HLA sensitisation is common in this situation [ 71 ]. Any possible benefits of HLA sensitisation by continuation of immunosuppression with a failing graft have to be balanced against the side effects and, in particular, the risk of infection in the patient on dialysis.…”
Section: Prevention Of Hla Sensitisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of nephrectomy and/or continuing immunosuppression to HLA sensitisation in the failing graft is not clear. Transplants that fail in the first year, or those that result from acute non-concordance with medications often present with acute rejection and systemic involvement, and frequently progress to nephrectomy; it is perhaps not surprising, therefore, that HLA sensitisation is common in this situation [ 71 ]. Any possible benefits of HLA sensitisation by continuation of immunosuppression with a failing graft have to be balanced against the side effects and, in particular, the risk of infection in the patient on dialysis.…”
Section: Prevention Of Hla Sensitisationmentioning
confidence: 99%
“…The impact of HLA sensitisation notwithstanding, the decision to perform nephrectomy needs to balance the risks (bleeding, sepsis) against clinical indications (tenderness and fever, or to create space for future transplants). Preservation of residual renal function on dialysis is clearly associated with improved cardiovascular outcomes [ 71 ]. However, the retention of a failed allograft is also associated with a chronic inflammatory state that can lead to anaemia, erythropoietin resistance and hypoalbuminaemia [ 79 ].…”
Section: Prevention Of Hla Sensitisationmentioning
confidence: 99%
“…before the modern immunosuppression era. In a more recent analysis of 18 children who underwent GN, none of the patients had major intra- or post-operative complications requiring a secondary operation, unplanned intensive care admission or blood transfusion within the first 14 days [ 2 ]. The surgical approach was not described.…”
Section: Outcomes After Gnmentioning
confidence: 99%
“…The alternative is surgical removal of the failed graft (graft nephrectomy [GN]). Previous studies have shown that more than half of children with failed renal allografts undergo GN [ 2 , 3 ], suggesting that GN occurs frequently in the pediatric RTR population. Children with graft failure within a year of transplantation are four times more likely to undergo GN [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation